Anticipatory management of enterprises on the basis of weak signals - Melnyk, Olga; Adamiv, Marta (Видавництво Львівської політехніки, 2013)
The main purpose of research is to ground the conceptual principles of enterprises anticipatory management on the basis of weak signals. In the paper the actuality of anticipatory management as an objectively necessary element of the enterprise management process in today rapidly changing and unpredictable business environment is grounded. The sequence of enterprises anticipatory management on the basis of weak signals is specified. The typology of weak signals of potential events by kinds of enterprise activity is developed.
Keywords: anticipatory management; weak signals; technology; functions; methods; decisions; kinds of enterprise activity